2005
DOI: 10.1210/en.2004-0485
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of Steroidogenesis in Immature Rat Leydig Cells Evoked by Interleukin-1α Is Potentiated by Growth Hormone and Insulin-Like Growth Factors

Abstract: The cytokine IL-1alpha is produced constitutively by the intact testis, but its function in this organ remains largely unknown. In this study we examined cooperation between IL-1alpha and GH and IGFs with regard to stimulation of steroidogenesis by Leydig cells from 40-d-old rats in vitro. IL-1alpha alone stimulated testosterone (T) and dihydrotestosterone (DHT) production. GH, IGF-I, or IGF-II alone was without effect on T production, but they were found to elevate DHT release, albeit without an obvious dose-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 64 publications
1
38
0
Order By: Relevance
“…Shortly after the testicular phenotype of the NKX2-1 null mice was described, we reported that fetal mouse Leydig cells express the melanocortin type 2 receptor, the receptor for ACTH. Furthermore, we showed that ACTH would stimulate androgen production in fetal and neonatal testes but not in adult (Amir et al 1978, Weiss-Messer et al 1996, Colon et al 2005), but there is little evidence of effects on the fetal Leydig cells. In the human fetus, the second trimester pituitary secretes prolactin (PRL), and the PRL receptor is expressed in the testis, but there is no correlation between PRL and testosterone (Fowler et al 2008(Fowler et al , 2009).…”
Section: Endocrinology Of the Fetal Testismentioning
confidence: 76%
“…Shortly after the testicular phenotype of the NKX2-1 null mice was described, we reported that fetal mouse Leydig cells express the melanocortin type 2 receptor, the receptor for ACTH. Furthermore, we showed that ACTH would stimulate androgen production in fetal and neonatal testes but not in adult (Amir et al 1978, Weiss-Messer et al 1996, Colon et al 2005), but there is little evidence of effects on the fetal Leydig cells. In the human fetus, the second trimester pituitary secretes prolactin (PRL), and the PRL receptor is expressed in the testis, but there is no correlation between PRL and testosterone (Fowler et al 2008(Fowler et al , 2009).…”
Section: Endocrinology Of the Fetal Testismentioning
confidence: 76%
“…In line with this hypothesis, boys with a genetic deficiency in production of this growth factor are undermasculinized, suggesting a lack of androgen production by their fetal Leydig cells [30]. As stated above GH and IGF-I may also act as survival factors for Leydig cells [31,32]. Thus, all of these factors appear to work in concert to trigger the processes that control the differentiation, maturation and regression of human fetal Leydig cells.…”
Section: Developmental Regulation Of Fetal Human Leydig Cellsmentioning
confidence: 94%
“…Even though most of the physiologic functions of IGF-I are thought to occur via IGFR (29), surprisingly, in newborn testes only moderate staining of IGFR in ICs and LCs was observed, whereas during the postnatal activation period, poor expression was also found in LCs. It is interesting that, Colon et al (16) recently found that both IGF-II and insulin phosphorylate/activate rat testis IGFR in the same manner as IGF-I, suggesting that all of these factors activate common signaling pathways in LCs.…”
Section: Discussionmentioning
confidence: 99%
“…Growth factors such as IGF and insulin through endocrine, autocrine, and paracrine regulatory events are known to play diverse roles in steroidogenesis (16,23,35). Hence, it could be proposed that, in the absence of LH, IGFs, via IGFR and/or IR, might induce the synthesis of androgens in precursor LC fibroblast.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation